Urbanisation and sexual health: Understanding bisexually active men in Hanoi, Vietnam - Higgs, Peter; Reddel, S.; Pham, H.; Dang, K.; Hellard, M. (Routledge, 2014)
Background: Men who have sex with men (MSM) in Vietnam are receiving increased attention in recognition of their high-risk behaviours and potential for human immunodeficiency virus(HIV) infection and transmission. Due to societal pressures, many MSM in Vietnam are also bisexually active, which ultimately increases the transmission risks beyond the MSM population. Evidence is emerging that indicates a greater proportion of women in Asia with low-risk sexual activities are contracting HIV from their male partners who have become HIV infected through male–male sex. Methodology: Fourteen focus group discussions exploring sexual and social networks were conducted in Hanoi between July 2010 and September 2010. A total of 96 individuals participated in these sessions. Findings: A risk environment approach was used to analyse the focus group themes of social stigma and marriage, sex with other men in closed settings and transactional sex in Hanoi, an increasingly urbanising and westernising city. Implications: Despite limited evidence globally that bisexual men act as a bridge for sexually transmitted diseases, there is particular concern in Vietnam about this potential risk. HIV rates amongst MSM are rapidly rising and there are reports of women contracting HIV from their male partners who are bisexually active.